(untitled) (Training and Practice : Journal of Educational Sciences, 2016)
Problems which block the renewal of didactics will be identified based on our research, which was supported by the Hungarian Academy of Science in 2015. Our research question was whether and in which way ICT supports the teaching and learning of mathematics in school, and we aimed at finding “best practices” for using ICT, too. Up to now, we have preformed classroom research in several grades of primary school (with 13 and 15-year old pupils). We looked for the opportunities of psychological and pedagogical renewal, and a first standard monitoring criteria has been developed and used. Based on our research we can firmly state that it is urgent to develop extensively the ICT competences of teachers, otherwise there is little hope of developing new didactics in Hungary.